Decarbonization pathways and energy investment needs for developing Asia in line with 'well below' 2°C. (7th February 2020) - Zhou, Wenji; McCollum, David L.; Fricko, Oliver; Fujimori, Shinichiro; Gidden, Matthew; Guo, Fei; Hasegawa, Tomoko; Huang, Han; Huppmann, Daniel; Krey, Volker; Liu, Changyi; Parkinson, Simon; et al.
ABSTRACT: Exploring potential future pathways for developing Asia's energy consumption, CO2 emissions and infrastructure investment needs is essential to understanding how the countries of this rapidly growing region may contribute to the global climate targets set out in the 2015 Paris Agreement. To this end, this study employs the state-of-the-art global integrated assessment model MESSAGEix-GLOBIOM to investigate mid-century decarbonization strategies for developing Asia to 2050. Our results indicate that a radical change in the energy portfolio is required to reach the target of 'well below' 2°C. Specifically, our scenarios point to a rapid reduction of fossil fuel utilization, enhancement of low-carbon energy supply, and boosting of energy efficiency efforts. Such a transformation leads to a deep cut in CO2 emissions by 78% and 93% by 2050 in scenarios consistent with the 2°C and 1.5°C targets, respectively. Electricity generation and final energy consumption become dominated by low-carbon energy by 2050 in these scenarios. In terms of investment needs beyond a baseline scenario, the 2°C and 1.5°C pathways imply that the scale of low-carbon investment may need to double and triple, respectively. These increases would be partially offset by disinvestment in coal, oil and natural gas extraction and conversion infrastructure. Decarbonizing the energy system also impacts the capital needed for making progress on other sustainable development goals (SDGs), such as air pollution, clean water and food security. Key policy insights Governments will need to employ a variety of policy mechanisms, including mandates and subsidies for renewables and electric vehicles, efficiency standards for end-use technologies, and bans on free-emitting fossil fuel plants, among others. Relative to the baseline scenario for developing Asia, the scale of investment into low-carbon energy to 2050 may need to double for a 2°C scenario, and to triple for 1.5°C. Policy instruments such as green finance are essential for this region to mobilize a broadened channel of investment, particularly from the private sector. Low-carbon investment would significantly reduce the capital investment needed to achieve the SDG target for air quality, but increase the requirements for meeting targets on clean water and food security, though only to a small extent.